Complication Rate in Minimally Invasive Revision Lumbar Discectomy: A Case Series and Technical Note. Issue 5 (June 2018) - Felbaum, Daniel R.; Stewart, Jeffrey J.; Distaso, Casey; Sandhu, Faheem A.
Abstract : Revision lumbar discectomy, given the disruption of anatomic planes, can be a more technically complicated operation. Historically, it may have higher complication rates than first-time microdiscectomy. Recently, minimally invasive tubular discectomy (MITD) has been reported as an equivalent treatment to traditional approaches and may have better utility for revision surgery. A retrospective review of MITDs performed by the senior surgeon (F.A.S.) on 42 patients with single-level, recurrent disk herniation was analyzed. Surgical technique, preoperative and postoperative visual analogue score, modified Macnab criteria, and complication rate were compared with similar patient series in the literature. One case is reviewed and the technique is described in detail. There were no significant differences across age (49.5±14.1), sex, or obesity status. Visual analogue scores improved significantly from 7.24±1.75 to 2.45±2.12 ( P <0.001). Successful clinical outcome (excellent or good Macnab score) was reported in 83.3% of patients. There were no postoperative complications, including dural tears or wound infections: fewer than any reported series of this size to date. MITD can be safely performed for revision discectomies with low morbidity. A paramedian approach helps to decrease the exposure to preexisting scar tissue and may offer a significant advantage over the traditional midline approach to treat recurrent disk herniation. Abstract : Supplemental Digital Content is available in the text.